Ocean : Reflections on a Century of Exploration - Berger, Wolfgang H. (Book collections on Project MUSE., 2009)
The past one hundred years of ocean science have been distinguished by dramatic milestones, remarkable discoveries, and major revelations. This book is a clear and lively survey of many of these amazing findings. Beginning with a brief review of the elements that define what the ocean is and how it works-from plate tectonics to the thermocline and the life within it-Wolf H. Berger places current understanding in the context of history. Essays treat such topics as beach processes and coral reefs, the great ocean currents off the East and West Coasts, the productivity of the sea, and the geologi.